Deferoxamine Treatment Effectively Prevents Periodontitis Progression by Reducing Inflammation and Osteoclastogenesis in Experimental Periodontitis Rats - Zhu Y; Qiao S; Pang Y; Wang H; Zhou Y (Journal of Inflammation Research)
Yanlin Zhu,1,2 Shuwei Qiao,2,3 Yuxuan Pang,2,3 Huimin Wang,2,3 Yanmin Zhou1,2 1Department of Dental Implantology, Hospital of Stomatology, Jilin University, Changchun, People’s Republic of China; 2Jilin Provincial Key Laboratory of Tooth Development and Bone Remodeling, Hospital of Stomatology, Jilin University, Changchun, People’s Republic of China; 3Department of Prosthodontics, Hospital of Stomatology, Jilin University, Changchun, People’s Republic of ChinaCorrespondence: Yanmin Zhou, Jilin Provincial Key Laboratory of Tooth Development and Bone Remodeling, Hospital of Stomatology, Jilin University, 1500 Qinghua Road, Changchun, Jilin Province, 130021, People’s Republic of China, Tel +8618943971001, Email zhouym@jlu.edu.cnPurpose: Although the anti-inflammatory properties of the hypoxia-mimetic drug deferoxamine (DFO) have been reported, its potential as a treatment for periodontitis remains unknown. This study investigated the therapeutic benefits of DFO on osteoclastogenesis and inflammation in periodontitis progression.Methods: RAW264.7 cells were pretreated with DFO before stimulation with lipopolysaccharides from Porphyromonas gingivalis (P.g-LPS). Hypoxia-inducible factor-1α (HIF-1α) and inflammatory factors were measured, followed by analysis of relevant inflammatory pathways. Immunofluorescence and molecular biology methods were employed to assess osteoclast differentiation in RAW264.7 cells after nuclear factor-κB ligand (RANKL) induction. A rat model of periodontitis was es\lished using ligature wires, and alveolar bone loss was assessed via micro-computed tomography. Osteoclastogenesis and periodontal inflammation were assessed through immunohistochemistry as well as hematoxylin and eosin staining.Results: DFO reduced the P.g-LPS-induced inflammatory factor expression (P < 0.0001) and upregulated HIF-1α (P = 0.0278) in RAW264.7 cells. DFO suppressed NF-κB signaling by inhibiting NF-κB p65 nuclear translocation and phosphorylation. DFO pretreatment inhibited osteoclast development by decreasing F-actin rings synthesis, reducing the number of mature osteoclasts (P < 0.0001) and downregulating osteoclast-specific markers (P < 0.05). In rat periodontitis models, DFO treatment reduced tissue inflammation, osteoclastogenesis, and alveolar bone loss (P  < 0.05).Conclusion: DFO effectively prevented osteoclast development, alveolar bone loss, and inflammation associated with periodontitis.Keywords: deferoxamine, periodontitis, inflammation, osteoclast differentiation